Tendencies in spatial research: Results of an internet search - Gnest, Holger; Roggendorf, Wolfgang; Fürst, Dietrich (Raumforschung und Raumordnung | Spatial Research and Planning, 2000)
To prepare the research framework 2000–2005 of the Academy for Regional Research and Regional Planning, a search in relevant internet sources from the fields of research, consultancy and administration was carried out. The interpretation could not be absolutely representative since the information supply was very different. Nevertheless, some topics can be regarded as “big issues”: Implementation and design of sustainability, spatial development in the context of globalization of economy, politics and society, world wide connected cities and agglomerations, the effect of scientific progress, especially in information technology, transport and the changing role of the state and its institutions. Finally some conclusions are drawn concerning the investigation methods and how to deal with these big issues.
Keywords: Article